An Optimality Theoretic analysis of Yoruba hypocoristic personal names: Issues of truncation, reduplication and tone - Ehineni, Taiwo Oluwaseun (Stellenbosch Papers in Linguistics Plus, 2023)
This paper provides an Optimality Theoretic analysis of Yoruba hypocoristic personal names with the aim of showing the interaction of different linguistic processes in the formation of Yoruba names. Based on the data collected from Yoruba texts and interactions in the speech community, this study demonstrates that the formation of the hypocoristics involves not only processes of shortening or reduplication, but also tonal truncation. While Akinlabi and Liberman (2000) note that Yoruba has tonotactic restrictions—where especially vowel-initial words can only take a low or mid tone but not a high tone—, this study reveals that such restriction may be violated in formation of hypocoristics, where reduplicated forms tend rather to satisfy a tonal requirement of HHML to be well-formed. Crucially, the study shows that deriving the hypocoristic in Yoruba involves processes relating not only to the foot structure (foot binarity), where the base of the derived form is expected to be a binary foot, but also, and essentially, processes relating to the tonal structure.